Knee and Ankle Exoskeletons for Motor Rehabilitation: A Technology Review - Huamanchahua, Deyby (2022)
Exoskeletons have been around since 1890 when a passive device was developed to assist movement. Although the exoskeleton initially focused on the whole body, it has become increasingly focused on a more specific area, which makes rehabilitation work more feasible and, consequently, less costly. Therefore, the purpose of the article is to present a systematic review of trends in the technical area of knee and ankle exoskeletons for rehabilitation purposes. The objective is to provide the interested researcher with a structured matrix that integrates essential components and mechanisms in the development of knee and ankle exoskeletons. As a methodology, specialized databases in biomechanics were used that aided in the collection of research conducted between 2019 and 2022. The filtering process resulted in the selection of 37 investigations. Finally, it was concluded that innovations in exoskeletons contribute to patient rehabilitation and that there is still room for further improvement in the implementation of projects on a commercial scale and the development of new exoskeletons based on previous research.